Four-dimensional flow cardiac magnetic resonance assessment of left ventricular diastolic function - Ashkir, Zakariye; Myerson, Saul; Neubauer, Stefan; Carlhäll, Carl-Johan; Ebbers, Tino; Raman, Betty (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular diastolic dysfunction is a major cause of heart failure and carries a poor prognosis. Assessment of left ventricular diastolic function however remains challenging for both echocardiography and conventional phase contrast cardiac magnetic resonance. Amongst other limitations, both are restricted to measuring velocity in a single direction or plane, thereby compromising their ability to capture complex diastolic haemodynamics in health and disease. Time-resolved three-dimensional phase contrast cardiac magnetic resonance imaging with three-directional velocity encoding known as ‘4D flow CMR’ is an emerging technology which allows retrospective measurement of velocity and by extension flow at any point in the acquired 3D data volume. With 4D flow CMR, complex aspects of blood flow and ventricular function can be studied throughout the cardiac cycle. 4D flow CMR can facilitate the visualisation of functional blood flow components and flow vortices as well as the quantification of novel haemodynamic and functional parameters such as kinetic energy, relative pressure, energy loss and vorticity. In this review, we examine key concepts and novel markers of diastolic function obtained by flow pattern analysis using 4D flow CMR. We consolidate the existing evidence base to highlight the strengths and limitations of 4D flow CMR techniques in the surveillance and diagnosis of left ventricular diastolic dysfunction.